2020
DOI: 10.1126/sciadv.aaw0158
|View full text |Cite
|
Sign up to set email alerts
|

Soft extracellular matrix enhances inflammatory activation of mesenchymal stromal cells to induce monocyte production and trafficking

Abstract: Mesenchymal stromal cells (MSCs) modulate immune cells to ameliorate multiple inflammatory pathologies. Biophysical signals that regulate this process are poorly defined. By engineering hydrogels with tunable biophysical parameters relevant to bone marrow where MSCs naturally reside, we show that soft extracellular matrix maximizes the ability of MSCs to produce paracrine factors that have been implicated in monocyte production and chemotaxis upon inflammatory stimulation by tumor necrosis factor–α (TNFα). Sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 62 publications
1
60
0
Order By: Relevance
“…Encapsulating MSC in injectable hydrogels is extensively explored to increase retention time and to modulate the cellular activity in situ ( Farhat et al, 2019 ; Wong et al, 2020 ) by providing the cells with a 3D microenvironment that protects and promotes an anti-inflammatory and regenerative response, see outline in Figure 1 . Techniques range from single cell encapsulation to larger scaffolds with macroporous structure ( Kim et al, 2019 ).…”
Section: Modulating the 3d Environment For Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Encapsulating MSC in injectable hydrogels is extensively explored to increase retention time and to modulate the cellular activity in situ ( Farhat et al, 2019 ; Wong et al, 2020 ) by providing the cells with a 3D microenvironment that protects and promotes an anti-inflammatory and regenerative response, see outline in Figure 1 . Techniques range from single cell encapsulation to larger scaffolds with macroporous structure ( Kim et al, 2019 ).…”
Section: Modulating the 3d Environment For Treatmentmentioning
confidence: 99%
“…Bone marrow-derived MSC were encapsulated in alginate-based hydrogels with different stiffnesses and pre-cultured prior to exposure to the inflammatory cytokine TNF-α. MSC preconditioned in the softer hydrogel in combination with TNFα had an improved effect in controlling monocyte turnover ( Wong et al, 2020 ). These studies demonstrate how intrinsic cues of the microenvironment impact cellular behavior that can be harnessed in improving the therapeutic potential of MSCs.…”
Section: Modulating the 3d Environment For Treatmentmentioning
confidence: 99%
“…It has been shown that matrix elasticity regulates the sensitivity of the MSCs to the inflammation in a manner that is dependent on actin polymerization and lipid rafts (Wong et al 2020). Softer matrices support the clustering of TNF-α receptors on the MSC surface by facilitating actin polymerization, which can induce the production of monocyte-regulating chemokines such as CCL2 and CCL7 as well as anti-inflammatory factors such as TSG-6 in higher amounts as compared with a stiffer matrix in response to TNF-α stimulation (Fig.…”
Section: Role Of Biomaterials In Msc-mediated Immunoregulationmentioning
confidence: 99%
“…Even though, the stem cells are features of distinguishable toward the immuno-modulation and immuno-suppression properties. [25][26][27][28] Synergic methods, as well, a promising strategy and biocompatible, biodegradable materials are required for efficient cardiac stem cells transplantation to associate the treatment for AMI. Hence, a pouch-like hydrogel materials like collagen, gelatin, and fibroin can serve as a potential and medically advantageous candidate in drug delivery systems, cell therapy, creation and regeneration of muscle tissues, and controlled release of systems.…”
Section: Introductionmentioning
confidence: 99%
“…Even though, the stem cells are features of distinguishable toward the immuno-modulation and immuno-suppression properties. 25 - 28 …”
Section: Introductionmentioning
confidence: 99%